2007
DOI: 10.1016/j.bbamem.2007.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Structure and conformation of the disulfide bond in dimeric lung surfactant peptides SP-B1–25 and SP-B8–25

Abstract: Raman spectroscopy was used to determine the conformation of the disulfide linkage between cysteine residues in the homodimeric construct of the N-terminal alpha helical domain of surfactant protein B (dSP-B(1-25)). The conformation of the disulfide bond between cysteine residues in position 8 of the homodimer of dSP-B(1-25) was compared with that of a truncated homodimer (dSP-B(8-25)) of the peptide having a disulfide linkage at the same position in the alpha helix. Temperature-dependent Raman spectra of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 66 publications
6
29
0
1
Order By: Relevance
“…material). Generally, our Raman assignments correlate with those in the literature [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. The Raman spectrum of the SC is dominated by vibrational bands of its structural proteins, lipids, and tissue water.…”
Section: Resultssupporting
confidence: 86%
“…material). Generally, our Raman assignments correlate with those in the literature [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. The Raman spectrum of the SC is dominated by vibrational bands of its structural proteins, lipids, and tissue water.…”
Section: Resultssupporting
confidence: 86%
“…This proposed splayed structure of the helix dimer is supported by Raman and polarized FTIR spectroscopy studies performed on the SP-B 1-25 and SP-B 8 -25 disulfide linked dimer. While the disulfide linkage is strained, it can clearly permit dimer helical splays and surface dependent helix orientation in surfactant lipids, in agreement with our proposed model (6). Additionally, recent work on lung surfactant peptoids, or peptide mimics, showed that the linkage of monomers by a rigid triazole moiety to form a dimer enhanced in vitro surface activity in a lipid film relative to its monomeric counterparts (16).…”
Section: L343 Importance Of Sp-b Nh2-terminal Insertion Sequencesupporting
confidence: 84%
“…While there are no high-resolution crystal or NMR structures of the native SP-B protein, the structure of the NH 2 terminus up to residue 25 is well defined as determined by a combination of NMR, FTIR, and Raman spectroscopy (6,22,38,53,59,71). Residues 1-9 (FPIPLPYCW), proposed to act as an "insertion sequence," comprise a hydrophobic region containing a poly-proline-like sequence.…”
mentioning
confidence: 99%
“…Because prior results with SP-B peptides [17,18,58,63,79,80] suggested that the N-terminal sequence (i.e., residues 1–7) plays key roles in the surfactant properties of full-length SP-B, we next engineered the Super Mini-B (S-MB), a 41-residue peptide mimic in which residues 1–7 was covalently attached to the N-terminus of MB [S-MB (residues 1–41): FPIPLPYCWLCRALIKRIQAMIPKGGRMLPQLVCRLVLRC]. S-MB might be expected to show higher surfactant activity than MB, because the former peptide may more accurately mimic the leaflet structure containing the N- and C-terminal domains of SP-B (Figure 1).…”
Section: Mini-b (Mb) and Super Mini-b (S-mb) Synthetic Peptidesmentioning
confidence: 99%